2017
DOI: 10.1136/jnnp-2017-316365
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the pathoanatomy of amyotrophic lateral sclerosis in vivo: targeting a propagation-based biological marker

Abstract: ObjectiveNeuropathological studies in amyotrophic lateral sclerosis (ALS) have shown a dissemination in a regional sequence in four anatomically defined patterns. The aim of this retrospective study was to see whether longitudinal diffusion tensor imaging (DTI) data support the pathological findings.MethodsThe application of DTI analysis to fibre structures that are prone to be involved at each neuropathological pattern of ALS was performed in a monocentre sample of 67 patients with ALS and 31 controls that ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
149
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(164 citation statements)
references
References 38 publications
15
149
0
Order By: Relevance
“…Validating our simulated impairment using the later stage empirical impairment of individual patients, our model offers a new network‐based perspective on ALS as a progressive disease. The impairment level of certain brain regions has been shown to be closely related to clinical outcome measures . We demonstrated that the simulated aggregation levels correlate with empirical impairment at the level of brain regions and also with future clinical UMN burden.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Validating our simulated impairment using the later stage empirical impairment of individual patients, our model offers a new network‐based perspective on ALS as a progressive disease. The impairment level of certain brain regions has been shown to be closely related to clinical outcome measures . We demonstrated that the simulated aggregation levels correlate with empirical impairment at the level of brain regions and also with future clinical UMN burden.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, we demonstrated a consistency between the microscopic pathological staging in ALS and its representation on the macroscopic level of brain regions. This overlap may potentially facilitate tracking disease spread and categorizing patients into disease stages in vivo based on MRI . This result brings the 2 fields of pathological staging and in vivo MRI staging closer together as a crucial step toward combining all available patient information to understand ALS disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI studies have consistently shown motor and extra-motor grey matter atrophy (Murphy, Henry, & Lomen-Hoerth, 2007;Omer et al, 2017) and correlation between motor system pathology with ALSFRS-R (Bede et al, 2013;Kassubek et al, 2018;Schmidt et al, 2014;Walhout et al, 2015). Consequently, we first sought to correlate the alterations in connectivity within motor and frontal networks (Kay, Lesser, & Coltheart, 1992) and the Boston Naming test (Graves, Bezeau, Fogarty, & Blair, 2004).…”
Section: Correlates Of Eeg With Mri Neuropsychology and Disease Sementioning
confidence: 99%
“…Diffusion MRI techniques, such as diffusion tensor imaging (DTI) have been established to study integrity of neuronal tracts in vivo in the human brain. DTI studies found alterations of fiber tract integrity in neurodegenerative diseases like Alzheimer's disease and ALS (18)(19)(20)(21), including callosal involvement (22)(23)(24). An observational study found a consistent reduction in fractional anisotropy in the corpus callosum of ALS patients, extending rostrally, and bilaterally to the region of the primary motor cortices (23).…”
Section: Introductionmentioning
confidence: 99%